Analisis nilai karakter cerita nonfiksi dalam buku siswa kelas iv tema 7 “indahnya keragaman di negeriku” - Puji Prissetya Utami; Retno Winarni; Anesa Surya (Didaktika Dwija Indria, 2022)
Abstract. This research is a research with a qualitative descriptive approach. This research was conducted through several stages, namely reduction, classification, presentation, and drawing conclusions. This study aims to describe the character values of non-fiction stories contained in the fourth grade student book with the theme "The Beauty of Diversity in My Country" in the 2013 curriculum. These character values consist of religious values, nationalism values, independent values, mutual cooperation values, and integrity values. The research data source is the fourth grade student book theme 7 "The Beauty of Diversity in My Country" curriculum 2013. The results show the values of religious character, nationalism values, independent values, mutual cooperation, and integrity values can be instilled in students through non-fiction literary works.